2007
DOI: 10.1093/rheumatology/ken010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of biologic therapy on return to work in people with work disability due to ankylosing spondylitis

Abstract: Treatment of active AS with TNF blockade appears to be associated with improved capacity for work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 21 publications
2
40
1
2
Order By: Relevance
“…The level of employment of those who were of working age in this cohort of AS patients (60%) was approximately 14% lower than the current UK national average of those of working age (30). Similarly, a Dutch study demonstrated employment rates of 54.2% for an AS cohort, a significant reduction of 11% compared with the Dutch workingage population (10).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The level of employment of those who were of working age in this cohort of AS patients (60%) was approximately 14% lower than the current UK national average of those of working age (30). Similarly, a Dutch study demonstrated employment rates of 54.2% for an AS cohort, a significant reduction of 11% compared with the Dutch workingage population (10).…”
Section: Discussionmentioning
confidence: 54%
“…Hence the results are likely to be more generalizable than other studies. For example, previous UK-based studies have used the National Ankylosing Spondylitis Society (NASS) or just one centre to draw their sample from (13,30).…”
Section: Discussionmentioning
confidence: 99%
“…18 Studies on the effects of TNF antagonists on work limitations in RA patients have had either a retrospective observational design or a clinical primary outcome with work data examined as a secondary outcome. [19][20][21][22][23][24] These studies show an improvement in employability and a reduction in the workday losses in patients with RA and ankylosing spondylitis through the treatment with biologics (TNF antagonists). 17,23,25 In the present study, we examined the correlation between changes in work productivity and disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…Several instruments have been developed, but they provide different results (2,7,8,17,(21)(22)(23)(24). Among the instruments for presenteeism assessment, a self-reported measure of productivity at work might be a relevant indicator for future adverse work outcomes, like sick leave, because it accounts not only for symptoms such as pain, stiffness, and fatigue, but also for the effects of these symptoms on working speed, concentration, and interpersonal interactions.…”
Section: Introductionmentioning
confidence: 99%